(untitled) (Actual Problems of Psychology in Educational Institutions, 2021)
The article is devoted to the analysis of the phenomenology of the moral and psychological development of the individual in the modern conditions of the post-industrial society. It is stated that the formatting of the system of moral imperatives of modern youth is due to changes in the social space of public life; what has been said prompts the determination of trends in the assimilation of moral imperatives by young people in order to further optimize them. The article highlights the specific trends in the moral development of youth in an unstable information society. The emphasis is made on the humanistic and liberal views of philosophers on the peculiarities of the development of the moral properties of a person. beginquote